Politics and Culture In Indonesian Cinema - Pawito - (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2008)
This study deals with Indonesian cinema. Perspectives of politics and culture employed to provide understanding of how Indonesian cinema from the early period of its development untill the recent times. This study demonstrates that Indonesian cinema could be associated significantly with politics primarily in the 1950s and 1960s when Indonesian cinema had really started to grow. In the period of New Order cinema becomes a manifestation of kitsch pursuing for capital gain. Yet after the fall of the regime significant shifts occur namely no longer have Indonesian cinemas strongly related to politics in their content of messages but the cinemas promote much moore various discoursive contents.